Smallanthus sonchifolius roots ameliorate non-alcoholic fatty liver disease by reducing redox imbalance and hepatocyte damage in rats fed with a high fructose diet - Aleman, Mariano Nicolás (2019)
Objective: To evaluate the potential of Smallanthus sonchifolius (S. sonchifolius) roots in ameliorating hepatic damage of rats fed with a high fructose diet. Methods: The effect of S. sonchifolius roots on energy intake, body weight, fat and liver mass was determined in male rats fed with a high-fructose diet. Plasma glucose, triglycerides, total cholesterol, lipoproteins and aspartate aminotransferase and alanine aminotransferase were analyzed. Histological changes of the livers were evaluated by electronic microscopy and apoptosis was examined using the TUNEL method. The levels of malondialdehyde, reduced-glutathione and antioxidant enzymes (catalase, superoxide dismutase, glutathione peroxidase, glutathione S-transferase) activities were also determined. Results: S. sonchifolius roots significantly decreased energy intake, body weight, fat and liver mass (P < 0.05). S. sonchifolius roots ameliorated liver steatosis and mitochondrial morphology, avoiding cellular apoptosis and normalizing transaminase activity in the liver of rats fed with high fructose. Enzymatic assays revealed that S. sonchifolius roots had a modulatory effect on the oxidative stress induced by fructose-feeding by reducing lipid peroxidation (P < 0.05) and antioxidant enzyme activities (P < 0.05) in liver. Conclusions: S. sonchifolius roots can ameliorate non-alcoholic fatty liver disease by improving oxidative stress and liver injury.